PENGARUH MODEL PEMBELAJARAN KOPERATIF LEARNING TIPE TAKE AND GIVE TERHADAP HASIL BELAJAR MAHASISWA MATA KULIAH EKONOMI MONETER - Emilia Dewiwati Pelipa; Anna Marganingsih (JURKAMI : Jurnal Pendidikan Ekonomi, 2021)
This study aims to determine the effect of the Take and Give Model on student learning outcomes in monetary economics courses. The results showed that there was an increase in student learning outcomes in the experimental class using the take and give learning model, it was obtained an increase in learning outcomes of 30.08 with an average pretest value = 56.05 and an average posttest value = 87.03 while in the control class it was obtained an increase in learning outcomes of 25.00 with an average value of pretest = 58.9 and an average value of posttest = 83.09. Based on the results of hypothesis testing with a significance value (α), the Sig. (2-tailed) = 0.034 <0.05, then null hypothesis is rejected and alternative hypothesis is accepted. So it can be concluded that there are differences in student learning outcomes between the experimental class that uses the Take and Give Type of Cooperative Learning Model and the control class that uses the conventional learning model in monetary economics courses